Seven Paradoxes of Business Process Management in a Hyper-Connected World - Beverungen, Daniel; Buijs, Joos C. A. M.; Becker, Jörg; Di Ciccio, Claudio; van der Aalst, Wil M. P.; Bartelheimer, Christian; vom Brocke, Jan; Comuzzi, Marco; Kraume, Karsten; Leopold, Henrik; Matzner, Martin; Mendling, Jan; et al. (Business & Information Systems Engineering)
Business Process Management is a boundary-spanning discipline that aligns operational capabilities and technology to design and manage business processes. The Digital Transformation has enabled human actors, information systems, and smart products to interact with each other via multiple digital channels. The emergence of this hyper-connected world greatly leverages the prospects of business processes – but also boosts their complexity to a new level. We need to discuss how the BPM discipline can find new ways for identifying, analyzing, designing, implementing, executing, and monitoring business processes. In this research note, selected transformative trends are explored and their impact on current theories and IT artifacts in the BPM discipline is discussed to stimulate transformative thinking and prospective research in this field.
Keywords: Business process management (BPM); Social computing; Smart devices; Big data analytics; Real-time computing; BPM life-cycle

Tax Administrative Burden, Tax Relief and Investment during the Corona Crisis - Heile, Vanessa; Huber, Hans-Peter; Maiterth, Ralf; Sureth-Sloane, Caren

Populäre Kultur - Janus, Richard (Das Wissenschaftlich-Religionspädagogisches Lexikon im Internet)

Kompetenz- und professionsorientierte Didaktik. Grundform des Theologiestudiums - Reis, Oliver (Pfarrer oder Pfarrerin werden und sein. Herausforderungen für Beruf und theologische Bildung in Studium, Vikariat und Fortbildung)

Pirker, Viera / Juen, Maria: Religion – (k)ein Fach wie jedes andere. Spannungsfelder und Perspektiven in der kompetenzorientierten Leistungsbeurteilung. Stuttgart: Kohlhammer 2018 - Reis, Oliver (Theologischer Revue)

Grümme, Bernhard: Religionspädagogische Denkformen. Eine kritische Revision im Kontext von Heterogenität. Freiburg i.Br.: Verlag Herder 2019 - Reis, Oliver (Theologische Literaturzeitung)

Lernortspezifische Jugendtheologie als Marker religionspädagogischer Grundlage – ein Tagungsprotokoll - Reis, Oliver („Weil man halt ja nebenbei, so etwas gelernt hat…“. Lernortspezifische Jugendtheologie in Schule und Gemeinde)

Die Bibel als Medium religiöser Sprachentwicklung - Reis, Oliver; Lenze, Alina; Nagels, Johanna; Potthast, Fabian (Religion lernen. Jahrbuch für konstruktivistische Religionsdidaktik)

Machtvolle Differenzierungen: Wie Inklusionsdiskurse (religions-)pädagogische Praxis prägen - Brandstetter, Bettina; Reis, Oliver (Inklusive Religionspädagogik der Vielfalt. Konzeptionelle Grundlagen und didaktische Konkretionen)

Unisichtbar, lähmend oder steuernd. Heterogenität als didaktischer Akteur im Unterricht - Reis, Oliver (Heterogenität. Eine Herausforderung für Religionspädagogik und Erziehungswissenschaft)